Tibiotalocalcaneal nail fixation and soft tissue coverage of Gustilo–Anderson grade 3B open unstable ankle fractures in a frail population; a case series in a major trauma centre. Issue 4 (August 2018) - Armstrong, Lesley; Jackson, John; Riddick, Andrew
Highlights: We propose a surgical technique for open unstable ankle fractures in frail patients. Tibiotalocalcaneal nail fixation promotes early ambulation. The technique is associated with a low complication and re-operation rate. Abstract: Background: Gustilo–Anderson grade 3B open ankle fracture-dislocations requiring stable fixation and soft tissue coverage are increasingly common in frail populations. Methods: We identified all patients with open ankle fracture-dislocations treated with a tibiotalocalcaneal nail and soft tissue coverage over a five-year period. We retrospectively recorded pre-morbid status, fracture and soft tissue injury pattern, surgical details, post-operative mobility, length of hospital stay, complication and re-operation rate and survival. Results: 21 ankles (20 patients) are included, all grade 3B open fractures. All patients were permitted to mobilise by one to six weeks post-surgery. One patient required further soft tissue surgery. Six patients had superficial wound colonization/infection, none developed deep infections. None of the nails have required removal. We observed a 15% three-month mortality rate. Conclusion: Tibiotalocalcaneal nail fixation and soft tissue coverage of unstable open ankle fractures in frail patients facilitates early return to ambulation with a low complication and re-operation rate.